Sources of care in systems of control: understanding the perspectives and experiences of those supporting loved ones in community corrections - Uhlman, Anne, author; Opsal, Tara, advisor; Harney, Jessie, committee member; Mao, KuoRay, committee member; Nowacki, Jeff, committee member (Colorado State University. Libraries, 2025)
This dissertation examines the perspectives and experiences of Primary Support Persons (PSPs) who support a loved one while serving a sentence through community corrections. While a growing body of research explores the experiences of incarcerated individuals and their supports, little is known about those who provide care and resources to people under community supervision, despite this group representing the majority of the correctional population in the United States. This study addresses that gap by centering the voices of PSPs to understand how they conceptualize the role of community corrections, navigate their relationships, and experience the symbiotic effects of their loved one's supervision. The study draws on qualitative interview and survey data collected in collaboration with a community corrections agency. Findings demonstrate that PSPs play an essential yet largely unacknowledged role in sustaining community corrections. They provide critical emotional, instrumental, social, and informational support that enables clients to comply with supervision requirements, yet they also bear much of the system's burden, experiencing stigma, financial strain, emotional exhaustion, and state presence in their relationships. At the same time, many PSPs frame their involvement as acts of care and responsibility, revealing deep ambivalence toward a system that depends on their unpaid labor while offering limited recognition or support in return. By situating PSPs' accounts within broader theoretical frameworks of social support, responsibilization, and carceral reach, this research demonstrates how systems of control extend beyond those formally sentenced and into the lives of those who care for them. These findings complicate the boundaries between care and coercion in community corrections and underscore the need to recognize PSPs as key stakeholders in effective supervision and reentry practices.
Keywords: community corrections; critical criminology; alternative sentencing; social support; criminal justice